Global burden of cancer in adolescents and young adults aged 10–24 years: a trend analysis - Yang, Junjun; Luo, Guoping; Xiang, Qin; Li, Shuangliang; Feng, Yuan (Frontiers in Oncology, 2025)
BackgroundCancer is an important cause of human death. We aimed to analyze the cancer burden in adolescents and young adults aged 10–24 years at global, regional, and national levels from 1990 to 2021.MethodsWe analyzed global burden of disease (GBD) data from 1990 to 2021 to assess the cancer-related incidence, prevalence, death, disability-adjusted life-years (DALYs), and the corresponding age-standardized rates (ASRs) in adolescents and young adults aged 10–24 years by region, country, sociodemographic index(SDI), etiology and gender stratification. In addition, we evaluated health inequities caused by cancer burden from 1990 to 2021 and used bayesian age-period-cohort (BAPC) model to assess trend of the total cancer burden in adolescents and young adults aged 10–24 years.ResultsIn 2021, there were 235, 249.05(95%UI, 21, 7211.16 to 251, 1070.1) new cancer cases in adolescents and young adults aged 10–24 years and 94856.02 (95%UI: 85970.2 to 102769.63) deaths worldwide. In addition, there were 13499, 913.04 (95%UI, 1252506.95 to 1442998.32) prevalent cases and 6, 918, 657.72 (95%UI: 6, 254, 353.93 to 7, 480202.6) DALYs. Over the past 30 years, the age-standardized incidence rate (ASIR) and the age-standardized prevalence rate (ASPR) of total cancer in adolescents and young adults aged 10–24 years have increased globally, with the most significant increases in regions with high SDI, such as North America and parts of Europe and Asia. The age-standardized death rate(ASDR) and age-standardized DALY rate of total cancer have decreased significantly globally in adolescents and young adults aged 10–24 years. The ASDR and age-standardized DALY rate of total cancer in adolescents and young adults aged 10–24 years were highest in countries with lower SDI, particularly in South America and Africa. Among all regions, Tokelau, Niue, and Afghanistan had the highest ASDR in 2021. Among all cancers, leukemia, brain cancers and malignant neoplasm of bone & articular cartilage were the most common causes of cancer death in adolescents and young adults aged 10–24 years in 2021.ConclusionsGlobally, the total cancer burden of adolescents and young adults aged 10–24 years have increased significantly over the past 30 years. Differences in adolescent and young adult cancer burden were evident across regions with different SDI levels. Developing effective strategies to reduce the total cancer burden of adolescents and young adults was critical to promoting global equity and population health.